ANTICIPATING GLOBAL CLIMATE CHANGES BY USING ECOPEDAGOGY IN HISTORICAL STUDYIN INDONESIA UNIVERSITY OF EDUCATION - Maulana, Ikmal; Maharani, Citra; Aurisa, Halfiani (PEOPLE: International Journal of Social Sciences, 2015)
This article focused on the analysis of the study paradigm changes in one of historical subjects in Indonesia University of Education. Nowadays, historical study only focused on human activities in the past without seeing the human interactions with nature, and how the nature reacts to human being. It means that historical study which evolves nowadays is using anthropocentric paradigm which placed human being as the centre of life. Various disasters that happened should change the way people see anthropocentric paradigm to Ecocentrism. Based on the conditions, one of the historical subjects in Historical Study Department in Indonesia University of Education in evolve historical study using Ecopedagogy through this approach, students are expected to have ecological intelligences such as empathy for all forms of life, embracing sustainability as community practice, making something that invisible become visible, anticipating unintended consequences, and understanding how nature sustains life. Based on the research conducted using Ecopedagogy approach in historical study, students can realize, and implement the importance of building a good relation with nature as shown by historical event.